DEVELOPMENT OF A MATRIX MODULE TO IMPROVE YOUR UNDERSTANDING CAPABILITY OF MATHEMATICAL CONCEPTS - Laia, Nasib Baik (Universitas Nias Raya, 2023)
Mathematics subjects, which ideally are logical and useful subjects, have so far been less favored by students. The reality in schools is that there are still many who have difficulty understanding the concept of material, oneYof theYcausesYof thisYproblem is becauseY learningYis stillYteacher-centered and hasYnot been developed by the teacher's own teaching materials in learning. TheYpurpose ofYthis study was to develop aYmatrix module inYimproving theYabilityYtoYunderstand mathematical concepts.YThe type of researchYis research andYdevelopment (R&D), with the ADDIEYmodel (analyze, design, development, implementation, evaluation). Data collectionYtechniques are questionnaires, andYtests. Data analysisYtechniques are qualitative dataYanalysis and quantitative data analysis. Based on research and discussion that the results of the validation test from the validator show that it is very valid. The resultsYof the validationYof the material section obtained an average of 79.54% with a valid category. The results of the validation of media experts obtained an average of 92.59% with a very valid category and the results of the validation of linguists obtained an average of 90% with a very valid category. From the three validators, theYresults of the module validity obtained an average of 87.37% with a very valid category. practicality results were obtained based on limited class trials and field trials. The results of practicality in the limitedYclass trialYobtained results of 2.86 with a percentage of 71.5% in the very practical category. The results of practicality in field trials obtained results of 3.61 with aYpercentage of 90.25 and were categorized as very practical. The results of the effectiveness of the limited class trialYmodule with an average score of 0.80 in the high category, and the results of the effectiveness of the field class trial with theyacquisition of anyaverage scoreyof 0.66 inythe mediumYcategory. The developedYmodule is expected to beYused in improvingYthe ability to understand mathematical concepts in matrixYmaterial.